CONCURRENT EXERCISE INTERVENTION AND ITS EFFECT ON HYPERTENSIVE PATIENTS - Muhammad Irfan Badjuka; Abu Bakar; Arina Qona'ah (Biomedika, 2025)
Hypertension remains a major global health challenge due to its strong association with cardiovascular diseases and premature mortality. Lifestyle interventions, particularly physical activity, play a crucial role in managing hypertension. This systematic review aimed to analyze the effectiveness of concurrent training on blood pressure reduction in hypertensive patients. A systematic literature search was conducted across four databases (Scopus, ScienceDirect, PubMed, and Web of Science) from 2020 to 2025, following PRISMA guidelines. 8 studies (one RCT and seven quasi-experiments) involving 571 participants were included. The interventions ranged from 4 to 30 weeks, with most using treadmill walking or cycling for aerobic training and free weights or machines for resistance training. The results showed that seven out of eight studies reported significant reductions in blood pressure. Additionally, concurrent training was associated with improvements in body composition, functional performance, and health-related quality of life. The physiological mechanisms underlying these benefits likely include improved endothelial function, enhanced nitric oxide availability, and increased baroreflex sensitivity. This review concludes that concurrent training is an effective, safe, and holistic intervention for blood pressure management in middle-aged hypertensive populations.